Traces of the Unruh effect in surface waves - Barros, Guilherme B. [UNESP]; Rodrigues, João P. C. R. [UNESP]; Landulfo, André G. S.; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2020)
We look for classical traces of the Unruh effect in gravity waves. For this purpose, we start considering a white noise state of gravity waves on the surface of a water basin and calculate the two- and four-point functions of the Fourier transform of the surface height field with respect to accelerated observers. The influence of the basin boundaries and possible deviations from Gaussianity in the white noise state are considered in order to approximate conditions attainable in the laboratory. Eventually, we make the basin infinitely large in order to make contact between our classical results and quantum ones derived in free space. We hope that our results help to strengthen the bridge between the Unruh effect and this classical analog.